An Analysis of Cooperative Principles in Mark Twain's The Adventures of Huckleberry Finn (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
This research is a pragmatic analysis of The Adventures of Huckleberry Finn, a novel by Mark Twain, through Grice’s cooperative principle. The objectives of this research were to analyze the types and implied meanings and to examine the most frequent type of Grice’s cooperative principles performed by the main characters in the novel. This research employed a qualitative research approach by using the content analysis technique. The data were collated by analyzing the utterances that appear in the novel that indicated the disobedience cooperative principle. Grice’s cooperative principle found in this study consisted of two types: the first type was the observance maxim which included the maxim of quality, the maxim of quantity, the maxim of relation, and the maxim of manner. The second type was the non-observance maxim: flouting, violating, and opting out. The result showed that all types of Grice’s cooperative principles were found, and the maxim of violating was the most frequent type of Grice’s cooperative principle found in the novel.